Syura dalam Pemikiran Nurkhalis Madjid - N Nurkhalis (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2010)
Shura is a concept that has equivalence with democracy. Shura is identical for one model of Islamic democracy that has not been applied into the formal legal life. Nurcholish Madjid said that the Shura has been accepted by Muslims. Generally, Shura is equal, or near as democracy had teach by the Western. The scope of application of Shura concerned in world affairs only and not religious affairs. When The Prophet Muhammad life, he and his follower applied the Shura on every things except the God’s commandment . But after the he died, the caliphs are using agency deliberation to interpret the implementation of the ommandments of God. The result of deliberation constitution is a consensusto implement it in according to the needs and circumstances. The Shura decision making can be based on the majorities, minorities and experts or professionalizes.